Literature Review: Pola Makan Dan Aktivitas Fisik Pada Obesitas Remaja - Vionie Putri Istiqomah Istiqomah; Novera Herdiani (Universitas Nahdlatul Ulama Surabaya, 2020)
Obesity is a disease characterized by excessive storage of fat in fat tissue in the body. Obesity is becoming a health problem in the world and the increasing prevalence of adolescent obesity in both developed and developing countries. Adolescent obesity is important to note because the period of growth and development can change rapidly so that it affects the development of body composition and changes in weight. This study aims to find out the link between diet and physical activity in adolescent obesity. The research method uses traditional literature review, with the source of Google Scholar articles there are 9,990, Garuda Portal there are 24 and Pubmed there are 463 with a range of 2016-2020. Keywords are used in searches for articles